From Bilateral Periorbital Necrotic Wound to Fungal Brain Abscess: A Complicated Case of COVID-19-Associated Mucormycosis - Bahram Eshraghi; Nastaran-Sadat Hosseini; Rasoul Mohammadi; Seyed Hamid Reza Abtahi; Alireza Ramezani-Majd; Roya Azad; Mohsen Pourazizi (Case Reports in Infectious Diseases)
COVID-19-associated mucormycosis (CAM) is categorized as rhinocerebral-orbital (RCOM), pulmonary, gastrointestinal, cutaneous, and disseminated mucormycosis. An alarming surge in morbidity and mortality attributed to mucormycosis concurrent with coronavirus disease 2019 (COVID-19) has emerged as a cause for concern during the current outbreak of COVID-19. The global incidence of CAM has been attributed to environmental, host, and iatrogenic factors. Further, Mucorales interacting with epithelial cells followed by endothelium invasion are pivotal in developing mucormycosis in patients with COVID-19. In essence, CAM is an emerging condition that requires increased vigilance in all COVID-19 patients, including those who have recovered. In this case report, we describe a rare case of CAM in a 33-year-old immunocompetent man who developed bilateral periocular pain and a small area of cutaneous necrosis in both medial canthi associated with impaired vision, which progressed into a fungal brain abscess formation in the post-COVID period. Furthermore, this case aims to illustrate the potential underlying risk factors of CAM other than known risk factors, especially in immunocompetent individuals.